Improving the Capability of Addition and Subtract Accounting Operations using Problem based Learning (PBL) Elementary School - Munawaroh, Munawaroh (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The aim of this research is to improve the ability of addition and subtraction arithmetic operations using Problem Based Learning (PBL) in class I students at SD Negeri 2 Mayungan. This type of research is classroom action research with a research design in the form of planning, action and observation, and reflection. The research subjects were twenty-one class I students at SD Negeri 2 Mayungan. Data collection was carried out using tests and observations. The analytical method used is descriptive quantitative. Learning arithmetic operations using the PBL method requires students to enter into the given arithmetic operation problems. In PBL, the problem of adding and subtracting arithmetic operations that will be given is a contextual or real problem. The results of the research show that there has been an increase in the results of learning arithmetic operations using the PBL method. In the pre-test results, the average class percentage was 45% with insufficient criteria, then increased in cycle I to 63.3% with sufficient criteria. In cycle II the class average increased to 90% and was in very good criteria. It can be concluded that first grade students' ability to calculate addition and subtraction operations can be improved using the Problem Based Learning method.